PERSPECTIVES AND PRACTICES FROM INDONESIAN EFL TEACHERS ON LANGUAGE ADVISORS’ ROLES IN FOSTERING LEARNER AUTONOMY - Muhamad Ahsanu; Dyah Wijayawati (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2020)
Every teaching practitioner seemingly has come to a common term that language advising is essential in language learning especially in fostering language learner autonomy. However, the issue as to whether a teacher also plays the roles of an advisor or vice versa is still in controversy. This writing is not trying to claim which one is right and which one is not. This paper is just a little lantern on how actually the roles of a language advisor (LA) are exercised by teachers within the context of Indonesian EFL classrooms. Based on the data collected via interview suggest that they realized their role as a LA informally be it inside or outside their classroom practice. In actuating such LA roles, the teachers transformed into a motivator, awareness builder, student-teacher reflective practitioner, controller, and many times co-problem-solver. Presumably, the advising teachers in Indonesian setting not only feel responsible for transmitting knowledge and skills, but also for transforming ideas, advice, morality, values, etc. into their learners within and beyond classroom practices. The inkling of this paper is to descriptively address both theoretical and practical account of LA within the spectrum of learner autonomy.